Topical imiquimod compared with conization to treat cervical high-grade squamous intraepithelial lesions: Multicenter, randomized controlled trial - Polterauer, Stephan; Reich, Olaf; Widschwendter, Andreas; Hadjari, Laudia; Bogner, Gerhard; Reinthaller, Alexander; Joura, Elmar; Trutnovsky, Gerda; Ciresa-Koenig, Alexandra; Ganhoer-Schimboeck, Julia; Boehm, Ina; Berger, Regina; et al. (Gynecologic oncology, 2022)
In a previous phase II trial, we showed that topical imiquimod (IMQ) therapy is an efficacious treatment for high-grade squamous intraepithelial lesion (HSIL). Aim of the present study was to investigate the non-inferiority of a 16-week topical, self-applied IMQ therapy compared to large loop excision of the transformation zone (LLETZ) in patients diagnosed with HSIL. Phase III randomized, controlled, multicenter, open trial performed by Austrian Gynecologic Oncology group. Patients with histologically proven cervical intraepithelial neoplasia (CIN)2 (30 years and older) or CIN3 (18 years and older) and satisfactory colposcopy were randomized to topical IMQ treatment or LLETZ. Successful treatment was defined as negative HPV high-risk test result 6 months after start of the treatment. Secondary endpoints were histological outcome and HPV clearance rates. Within 3 years 93 patients were randomized, received the allocated treatment and were available for ITT analysis. In the IMQ group negative HPV test at 6 months after treatment start was observed in 22/51 (43.1%) of patients compared to 27/42 (64.3%) in the LLETZ group on ITT analysis (rate difference 21.2%-points, 95% two-sided CI: 0.8 to 39.1). In the IMQ group histologic regression 6 months after treatment was observed in 32/51 (63%) of patients and complete histologic remission was observed in 19/51 (37%) of patients. Complete surgical resection was observed in 84% after LLETZ. In women with HSIL, IMQ treatment results in lower HPV clearance rates when compared to LLETZ. LLETZ remains the standard for women with HSIL when treatment is required. Clinical Trial Registration: ClinicalTrials.gov Identifier: NCT01283763, EudraCT number: 2012-004518-32. •The study compared local Imiquimod therapy to LLETZ in patients diagnosed with HSIL.•HPV clearance was observed in 43% and 64% after Imiquimod and LLETZ, respectively.•LLETZ remains the standard therapy for women with HSIL when treatment is required.